Occurrence, origin, and risk assessment of metals in drinking water from a tropical suburban area (Jengka, Malaysia) - Sulaiman, Fazrul Razman; Mohamed, Noorfazira; Aris, Ahmad Zaharin (Springer, 2023)
Information about metal contamination in drinking water remains inadequate, especially for semi-urban areas. This study determines the concentrations of metals in drinking water in Jengka, Pahang, Malaysia. It also attempts to assess the potential health risks and to identify the possible sources of metal contamination. Metal concentration was analysed using inductively coupled plasma optical emission spectrometry. The results included the mean concentrations of Zn (1.7 × 10–1 mg/L), Pb (2.4 × 10–2 mg/L), and Cr (1.75 × 10–3 mg/L). In general, the concentration of metals was below the drinking water limitation standards set by the Malaysia Ministry of Health and the World Health Organization, except for Pb. This work estimates low potential non-cancer (HQ < 1) and low cancer risks (LCR < 1) from metal exposure. However, children appear to be more susceptible to metal exposure via drinking water than adults. Based on multivariate analysis, metal in drinking water could come from two sources. The findings suggest comprehensive continuous monitoring of metal concentrations from potable water, especially for semi-urban regions, to minimise health risks.